Sustainable Management Practices and Corporate Performance: A Global Bibliometric Study - Suhendi, Dedi; Adi Cahya, Willy (International Journal of Law Social Sciences and Management, 2026)
This study aims to analyze global trends, collaboration patterns, and research development directions related to sustainable management practices (SMP) and corporate performance using a bibliometric approach. In the context of increasing awareness of sustainability and corporate social responsibility, this study seeks to provide a comprehensive understanding of the relationship between sustainable management practices and corporate performance from a global perspective. The research method was conducted through bibliometric analysis based on secondary data taken from the Scopus and Crossref databases, with the selection process following the PRISMA guidelines. A total of 148 articles relevant to the topic of SMP and corporate performance were analyzed using VOSviewer software and Bibliometrix R-package to map collaboration networks, dominant keywords, and research thematic maps. The study showed a significant increase in publications between 2019 and 2024, with Environmental Science and Business Management as the main contributors. Key findings revealed that topics such as ESG (Environmental, Social, and Governance, corporate governance, and financial performance were the dominant focus and showed a positive relationship to increasing company competitiveness. Furthermore, there was a shift in research trends towards the integration of technologies such as machine learning and artificial intelligence in sustainability management. The implications of this research emphasize the importance of implementing SMP not only as an ethical obligation, but as a long-term business strategy that is able to increase the efficiency, innovation, and profitability of the company, as well as providing a new direction for the development of corporate sustainability policies at the global level.